2020
DOI: 10.22541/au.160226611.11924322/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Pour Point Depressants Combined with Dispersants on the Cold Flow Properties of Biodiesel-Diesel Blends

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Lin et al recently reported the synthesis of the terpolymers of C14 or C16 n -alkyl methacrylate, benzyl methacrylate (BM) and N -vinylpyrrolidone (NVP) [ 160 ] by free-radical copolymerization on the basis of 1–20:1:1 comonomer ratios ( Scheme 8 ). Similar copolymers, based on C12, C14, C16 and C18 alkyl methacrylates, were studied by Su et al as PPDs for the blends of the waste cooking oil BD (38.4 wt% of saturated FAMEs, CP = 7 °C, PP = 5 °C) with petroleum diesel (CP = −1 °C, PP = −12 °C) [ 161 ].…”
Section: Polymer Additives For Bd/petroleum Diesel Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al recently reported the synthesis of the terpolymers of C14 or C16 n -alkyl methacrylate, benzyl methacrylate (BM) and N -vinylpyrrolidone (NVP) [ 160 ] by free-radical copolymerization on the basis of 1–20:1:1 comonomer ratios ( Scheme 8 ). Similar copolymers, based on C12, C14, C16 and C18 alkyl methacrylates, were studied by Su et al as PPDs for the blends of the waste cooking oil BD (38.4 wt% of saturated FAMEs, CP = 7 °C, PP = 5 °C) with petroleum diesel (CP = −1 °C, PP = −12 °C) [ 161 ].…”
Section: Polymer Additives For Bd/petroleum Diesel Blendsmentioning
confidence: 99%
“… Effects of 1000 ppm ( a – c ), 2000 ppm ( d – f ), and 3000 ppm ( g – i ) RMC-BM-NVP terpolymers on ΔCP, ΔCFPP, and ΔPP of B20 (RMCMB-NVP = methacrylate-benzyl methacrylate- N -vinyl-2-pyrrolidone terpolymers, R = C12, C14, C16, C18). Reprinted with permission from [ 161 ]. Copyright (2020) Wiley-VCH Verlag GmbH & Co. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…One of the major technical obstacles that hinders the developments and application of biodiesel fuels is their poor low-temperature flow properties, which may cause blockage of the oil pipelines and filter because of the crystallization of the saturated fatty acid methyl esters with high melting points in biodiesel fuels [4][5][6][7]. Nevertheless, many methods can be used to mitigate this problem, such as modifying structures [8,9], winterization [10,11], adding pour point depressants [12][13][14], and blending with diesel [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols, such as ethanol (ET) and 1-butanol (BT), are primarily bio-based renewable energy because they are derived from the fermentation of renewable biomass [21][22][23]. Many researchers have investigated the effect of blending alcohols with biodiesel or diesel on the cold flow properties because of their relatively lower freezing points [14,24]. Hence, replacing the petrodiesel with biobased alcohols in ternary blends with biodiesel and DDCL to enhance the low-temperature flow properties of biodiesel is extremely possible.…”
Section: Introductionmentioning
confidence: 99%